SOSIALISASI HUKUM RIBA TERHADAP PENGGUNA GOPAYLATTER DI DESA BERINGAN KECAMATAN ALALAK KABUPATEN BARITO KUALA - Masrina, Masrina; Hasanah, Ikhwatun; Musthofa, Khabib; Andira, Ayu (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Islamic ban of usury is an attempt to eradicate economic injustice. This is against Islamic teachings, which emphasize helping the poor and middle class so that the wealthy don't take advantage of them. Reason being that Islamic economics teaches a commitment to social order and humanity, while also rejecting the idea of injustice and the vicious cycle it creates, which in turn leads to poverty. Users of Gopaylartter in Beringin Village, Alalak District, Barito Kuala Regency will be educated on usury legislation and given an overview of Islamic perspectives on debt and credit, which do not include usury. Although there are still obstacles to solve before Islamic banking can be more widely and effectively implemented, there have been good outcomes from socializing usury legislation on GoPayLater users, such as improved knowledge, comprehension, and interest.